Tissue Repair Laminate

A biodegradable polyurethane foam and barrier layer laminate addresses the challenge of balancing tissue ingrowth and adhesion resistance in abdominal wall repairs, facilitating effective tissue regeneration and natural decomposition.

JP7654729B2Active Publication Date: 2025-04-01POLYNOVO BIOMATERIALS PTY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023132690
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-22
Filing Date
2023-08-16
Publication Date
2025-04-01
Estimated Expiration
2038-12-21

AI Technical Summary

Technical Problem

Existing tissue repair devices struggle to balance tissue ingrowth with resistance to adhesions, particularly when used in abdominal wall repairs, and often require surgical removal due to non-biodegradability.

Method used

A biodegradable polyurethane foam layer with a pore structure for cell infiltration, combined with a polyurethane barrier layer having a surface resistant to adhesions, forming a tissue repair laminate that adheres to the abdominal wall while preventing adhesions with internal organs.

Benefits of technology

The laminate enables effective tissue regeneration by allowing tissue integration while minimizing postoperative adhesions, and it decomposes naturally, eliminating the need for surgical removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654729000013
    Figure 0007654729000013
  • Figure 0007654729000014
    Figure 0007654729000014
  • Figure 0007654729000015
    Figure 0007654729000015
Patent Text Reader

Abstract

To provide tissue repair laminates which promote cellular in-growth but also prevent or mitigate tissue adhesion.SOLUTION: The laminates comprise a biodegradable polyurethane foam layer which facilitates cellular infiltration and a polyurethane barrier layer which is non-adhesive to tissue. The laminates resist shrinkage under in vivo conditions and possess desirable mechanical properties. The laminates are used in, for example, the repair of herniated tissue, particularly, but not limited to, hernias in the abdominal wall.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001]

[0001] The present disclosure relates to tissue repair laminates that promote cellular ingrowth but also prevent or reduce tissue adhesions. The laminates comprise biodegradable polyurethanes and are used to repair, for example, herniated tissue, particularly, but not exclusively, hernias in the abdominal wall. [Background technology]

[0002]

[0002] Hernias occur when an organ pushes through a defect in the muscle or tissue that holds it in place, for example when the intestine may push through a weakened area in the abdominal wall. Hernias are most common in the abdominal wall, but also occur in other parts of the body, such as the upper thigh, groin, and navel. Inguinal (groin), hiatal (diaphragmatic), umbilical, abdominal, and incisional hernias are generally treated by surgical intervention.

[0003]

[0003] Various mesh materials have been proposed to strengthen the abdominal wall and close abdominal wall defects. Certain surgeries, including scar and umbilical hernia repair, may place the mesh in direct contact with sensitive abdominal viscera. Postoperative adhesions may develop between the mesh and the intestine, potentially resulting in complications such as intestinal fistula formation. As a result, repeat abdominal surgery is often required to repair complications resulting from adhesions. Intestinal obstruction due to adhesions causes over 2000 deaths annually in the United States.

[0004]

[0004] As mesh materials, biodegradable synthetic products, non-degradable synthetic products and biological products have been investigated. Examples include polypropylene, PTFE, polyester, and human or porcine derived dermal matrices. A suitable material is one that minimizes or eliminates the need for surgical removal, bonds well to the repair site but does not adhere to surrounding tissue, is hemostatic, and is ideally biodegradable.

[0005]

[0005] Polypropylene-based meshes have been used to reinforce soft tissues and close defects. However, polypropylene can form postoperative adhesions with abdominal viscera, such as the intestine, when used to repair inguinal hernias and other abdominal wall defects. Furthermore, polypropylene is not biodegradable. Thus, the implant must remain in the body and be surgically removed after the healing process, if necessary.

[0006]

[0006] Another material that has been used to prevent adhesions is an expanded polytetrafluoroethylene material sold as Gore-Tex®. However, this material is not hemostatic and is not biodegradable in the human body. Another material is a carboxymethylcellulose mesh barrier sold as Interceed®. However, this material cannot be applied in blood-rich environments because it rapidly loses its barrier function in such environments. Films formed from poly(ethylene oxide) and polyethylene terephthalate have also been proposed as barrier materials to prevent surgical adhesions.

[0007]

[0007] All meshes will form adhesions when placed adjacent to the intestine, but the degree of adhesion is determined by a number of mesh characteristics, including pore size, filament structure, and surface area. Heavy meshes induce a strong fibrotic reaction, which ensures strong adhesion to the abdominal wall, and also causes dense adhesions. In contrast, microporous materials cannot induce tissue ingrowth, and therefore have a very low risk of adhesion formation, but cannot strongly adhere to the abdominal wall.

[0008]

[0008] These extremes present the difficulty in producing a mesh that adheres well to the abdominal wall but not to the intestine. To alleviate these drawbacks, it has been proposed to coat tissue infiltratable meshes with adhesion-resistant barriers. The composite material so formed is placed surgically, thus the barrier isolating the sensitive viscera from the porous mesh and preventing the formation of postoperative adhesions. However, coating a sheet of tissue infiltratable mesh with a barrier layer may compromise the tissue infiltratability of the prosthesis.

[0009]

[0009] Another problem with many existing materials is that with use, scar tissue develops around the mesh, causing shrinkage. Summary of the Invention [Problem to be solved by the invention]

[0010]

[0010] Thus, there is a need for improved tissue repair devices for repairing tissue or muscle wall defects that exhibit acceptable tissue ingrowth characteristics but resist adhesion to sensitive organs or tissues. Such devices would further need to be biodegradable and resistant to shrinkage during use. [Means for solving the problem]

[0011]

[0011] Reference in this specification to any prior publication (or information derived therefrom) or any known matter is not, and should not be construed as, an acknowledgement or admission, or in any way suggesting, that that prior publication (or information derived therefrom) or any known matter forms part of the common general knowledge in the technical field to which this specification pertains.

[0012] In a first aspect, the present disclosure provides a method for producing a semiconductor device comprising: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; the second major surface of the barrier layer is less adhesiogenic than the first major surface of the foam layer; A tissue repair laminate is provided.

[0013] In a second aspect, the present disclosure provides a method for producing a semiconductor device comprising: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; the second major surface of the barrier layer adheres less to tissue than the first major surface of the foam layer; A tissue repair laminate is provided.

[0014] In a third aspect, the present disclosure provides a method for producing a semiconductor device comprising: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; the second major surface of the barrier layer being substantially non-adherent to tissue; A tissue repair laminate is provided.

[0015] In a fourth aspect, the present disclosure provides a method for producing a semiconductor device comprising: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; the second major surface of the barrier layer is substantially non-adhesion forming; A tissue repair laminate is provided.

[0016] In a fifth aspect, the present disclosure provides a method for producing a semiconductor device comprising: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; the second major surface of the barrier layer is substantially flat; A tissue repair laminate is provided.

[0017] In use, the first major surface of the foam layer faces the wound and the second major surface of the barrier layer faces the cavity.

[0018]

[0018] The tissue repair laminate is advantageous because, in use, the first major surface of the foam layer can be positioned facing, for example, the abdominal wall, and the second major surface of the barrier layer can be exposed to an internal organ. The barrier layer surface facing the internal organ is substantially resistant to adhesion, while the foam layer surface facing, for example, the abdominal wall, can adhere to tissue and facilitate tissue regeneration, for example abdominal wall regeneration.

[0019]

[0019] The tissue repair laminate of the present disclosure comprises: the laminate is substantially resistant to shrinkage in vivo; The laminate limits the occurrence of post-operative adhesions resulting from tissue repair; The foam layer allows for tissue integration; The barrier layer can be rendered substantially non-adherent to tissue during manufacture of the laminate; The barrier layer is substantially resistant to adhesions for extended periods in vivo; The laminate has higher mechanical strength than the foam layer alone; The laminate is synthetic and not biological; the method of manufacturing the laminate does not substantially affect the tissue ingrowth capabilities of the foam layer; and The foam layer or laminate can degrade over time and therefore does not need to be surgically removed. The present invention may have one or more of the following advantages:

[0020]

[0020] The foam layer may comprise a thermosetting polyurethane or may comprise a thermoplastic polyurethane. Preferably, the foam layer comprises a thermosetting polyurethane. Preferably, the foam layer comprises a crosslinked polyurethane.

[0021]

[0021] The barrier layer may comprise a thermoset polyurethane or may comprise a thermoplastic polyurethane. Preferably, the barrier layer comprises a thermoplastic polyurethane.

[0022]

[0022] The barrier layer can comprise a biodegradable polyurethane or a non-degradable polyurethane. Preferably, the barrier layer comprises a biodegradable polyurethane. The barrier layer can be designed to degrade at a different rate than the foam layer or at substantially the same rate.

[0023]

[0023] As used herein, the term "biodegradable" generally refers to the ability to be broken down by the normal functions of an organism / tissue, preferably into harmless, non-toxic or biocompatible products.

[0024] In some embodiments, the foam layer can degrade more quickly than the barrier layer.

[0025]

[0025] The tissue repair laminate has the following characteristics: (i) A suture retention strength of greater than 20N, or greater than 25N, or greater than 30N, or greater than 35N; (ii) An ultimate tensile strength of greater than 20 N / cm, or greater than 25 N / cm, or greater than 30 N / cm, or greater than 35 N / cm, or greater than 40 N / cm; (iii) a ball burst strength of greater than 100 N / cm, or greater than 125 N / cm, or greater than 150 N / cm, or greater than 175 N / cm, or greater than 200 N / cm; (iv) A tear resistance of more than 10N, or more than 15N, or more than 20N may include any one or more of:

[0026]

[0026] The tissue repair laminate may independently shrink less than 20%, or less than 15%, or less than 10%, or less than 5% of the surface area of ​​any surface after 10 days under in vivo conditions.

[0027]

[0027] The tissue repair laminate may independently shrink by less than 20%, or less than 15%, or less than 10%, or less than 5% in the surface area of ​​any of its surfaces after 20 days under in vivo conditions, or after 60 days under in vivo conditions, or after 90 days under in vivo conditions, or after 120 days under in vivo conditions, or after 200 days under in vivo conditions, or after 1 year under in vivo conditions, or after 2 years under in vivo conditions.

[0028] The foam layer may have a thickness of between about 0.1 mm and about 10 mm, or between about 0.2 mm and about 5 mm, or between about 0.3 mm and about 3 mm, or between about 0.3 mm and about 2 mm, or between about 0.4 mm and about 2 mm. The foam layer may have a thickness less than about 10 mm, or less than about 6 mm, or less than about 4 mm, or less than about 2 mm, or less than about 1 mm, or less than about 0.5 mm.

[0029]

[0029] Preferably, the foam layer has a thickness of between 0.3 mm and about 3 mm.

[0030] The barrier layer may have a thickness between about 20 μm and about 1000 μm, or between about 50 μm and about 500 μm, or between about 50 μm and about 400 μm.

[0031] In some embodiments, the foam layer has a thickness between about 0.3 mm and about 3 mm, and the barrier layer has a thickness between about 50 μm and about 400 μm.

[0032] In some embodiments, the foam layer has a thickness between about 0.3 mm and about 2 mm, and the barrier layer has a thickness between about 100 μm and about 300 μm.

[0033] In some embodiments, the foam layer has a thickness between about 0.3 mm and about 1 mm, and the barrier layer has a thickness between about 100 μm and about 300 μm.

[0034]

[0034] In some embodiments, the foam may be a non-reticulated foam. In some embodiments, the foam may be a reticulated foam. The foam may preferably have interconnecting pores. Preferably, the foam is a non-reticulated foam.

[0035]

[0035] As used herein, the term "non-reticulated" polyurethane foam refers to polyurethane foam that has not been subjected to a post-manufacturing process to remove the cell windows using either chemicals (e.g., alkaline solutions), heat (e.g., controlled hydrogen and oxygen combustion), or solvents.

[0036] In some embodiments, the foam may have a density between 3g / 100ml and 12g / 100ml, or between 4g / 100ml and 10g / 100ml, or between 5g / 100ml and 8g / 100ml.

[0037] In some embodiments, the porosity of the foam may be greater than 50%, or greater than 75%, or 80-95%, or 95-99.9%. It is desirable that the porosity should be as high as possible while maintaining other mechanical specifications. If the porosity is too low, the pores cannot interconnect. If the porosity is too high, the structural integrity of the foam may be mechanically compromised.

[0038] In some embodiments, the average pore size of the foam may be greater than 50 μm, or greater than 75 μm, or greater than 100 μm, or greater than 200 μm, or in the range of 100 to 600 μm, or in the range of 100 to 400 μm.

[0039] In some embodiments, the average pore size of the foam is in the range of 50 to 600 μm, or in the range of 60 to 600 μm, or in the range of 70 to 600 μm, or in the range of 75 to 400 μm, or in the range of 75 to 300 μm, or in the range of 100 to 300 μm.

[0040]

[0040] Preferably the average pore size of the foam is greater than 75 μm, more preferably between 100 and 300 μm.

[0041] In some embodiments, the tissue repair laminate has a mass of 50-800 g / m 2 Between 100 and 600 g / m 2 Between 200 and 500 g / m 2 The weight may be between 0.01 and 0.15.

[0042] In some embodiments of any of the aspects disclosed herein, the second major surface of the barrier layer is substantially non-adherent to tissue.

[0043]

[0043] Substantially non-adhesive means that, in some embodiments, the barrier layer does not adhere to tissue or adheres only to the extent that it can be easily peeled off from the tissue without damaging the tissue.

[0044] In some embodiments of any of the aspects disclosed herein, the second major surface of the barrier layer has a greater surface flatness than the first major surface of the foam layer. As used herein, the term "flat" with respect to a surface means that the surface is substantially non-adherent to tissue.

[0045] In some embodiments, the first major surface of the foam layer and the second major surface of the barrier layer are in direct contact with one another. In some embodiments, the first major surface of the foam layer and the second major surface of the barrier layer are fused to one another.

[0046]

[0046] In some embodiments, the laminate may include one or more additional layers disposed between the foam layer and the barrier layer. The one or more additional layers may be an adhesive layer.

[0047] Foam Layer

[0047] The biodegradable polyurethane foam layer may be biodegradable in an organism into biocompatible breakdown products.

[0048]

[0048] The polyurethane foam layer may be degradable in vivo. The polyurethane foam layer may be degradable at a temperature between about 35°C and about 42°C.

[0049]

[0049] The polyurethane foam layer can be degraded by hydrolysis. The polyurethane foam layer can be degraded by hydrolysis of the ester functional groups.

[0050] Polyol for foam layer

[0050] The polyurethane foam may be derived from one or more biodegradable polyols and one or more isocyanates. Alternatively, the polyurethane foam may be derived from a mixture of one or more biodegradable polyols and one or more non-biodegradable polyols, and one or more isocyanates. Preferably, the biodegradable polyol is a polyester polyol.

[0051]

[0051] The foam may be derived from one or more biodegradable polyols having a molecular weight of about 2000 daltons or less, or about 1500 daltons or less, or about 1300 daltons or less.

[0052]

[0052] The biodegradable polyol may have a molecular weight between about 200 and about 2,000 daltons, or between about 200 and about 1,500 daltons, or between about 200 and about 1,300 daltons, or between about 600 and about 1500 daltons, or between about 900 and about 1300 daltons.

[0053]

[0053] The biodegradable polyol may have a molecular weight of about 10,000 daltons or less, or about 8,000 daltons or less, or about 6,000 daltons or less, or about 4,000 daltons or less, or about 2,000 daltons or less, or about 1,500 daltons or less, or about 1,000 daltons or less, or about 800 daltons or less, or about 600 daltons or less, or about 500 daltons or less, or about 400 daltons or less, or about 350 daltons or less, or about 300 daltons or less.

[0054] The biodegradable polyol may have a molecular weight of less than 500 daltons, or less than 400 daltons, or less than 350 daltons, or less than 300 daltons.

[0055]

[0055] The biodegradable polyol may be in a liquid state at 20° C. and atmospheric pressure. Alternatively, the biodegradable polyol may be in a solid state at 20° C. and atmospheric pressure. In some embodiments, the polyol may be in the form of a mixture of solid and liquid at 20° C.

[0056]

[0056] The biodegradable polyols can be derived from one or more polyol initiators and one or more hydroxy acids, diacids or cyclic esters, and combinations thereof.

[0057] In some embodiments, the biodegradable polyols can be derived from one or more polyol initiators and at least one hydroxy acid.

[0058] In some embodiments, the biodegradable polyols can be derived from one or more polyol initiators and at least one diacid.

[0059] In some embodiments, the biodegradable polyols can be derived from one or more polyol initiators and at least one cyclic ester.

[0060] In some embodiments, the biodegradable polyol can be derived from one or more polyol initiators, at least one hydroxy acid, and at least one diacid.

[0061] In some embodiments, the biodegradable polyol can be derived from one or more polyol initiators, at least one hydroxy acid, and at least one cyclic ester.

[0062] In some embodiments, the biodegradable polyol can be derived from one or more polyol initiators, at least one diacid, and at least one cyclic ester.

[0063] In some embodiments, the biodegradable polyol can be derived from one or more polyol initiators, at least one hydroxy acid, at least one diacid, and at least one cyclic ester.

[0064]

[0064] The one or more polyol initiators can be pentaerythritol, trimethylolpropane, glycerol, 1,4-butanediol, ethylene glycol, sorbitol, glucose, sucrose, 1,2-propanediol, 1,3-propanediol, pentanediol, myo-inositol, hexamethylenediol, heptanediol, octanediol, nonanediol, decanediol, dodecanediol, 2-ethyl-1,3-hexanediol (EHD), 2,2,4-trimethylpentane-1,3-diol (TMPD), 1,4-cyclohexanedimethanol, diethylene glycol, dipropylene glycol, and combinations thereof.

[0065]

[0065] Non-limiting examples of hydroxy acids include l-lactic acid, d-lactic acid, d,l-lactic acid, mandelic acid, phenyl-lactic acid, hydroxybutyric acid, hydroxyvaleric acid or glycolic acid, and combinations thereof.

[0066]

[0066] Non-limiting examples of cyclic esters include ε-caprolactone, glycolide, lactide, mandelide and ρ-dioxanone, and combinations thereof. Biodegradable polyols can be prepared via ring-opening polymerization or condensation reactions.

[0067]

[0067] Non-limiting examples of diacids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid and hexadecanedioic acid, and combinations thereof.

[0068]

[0068] Biodegradable polyols can be prepared via a ring-opening polymerization reaction or a condensation reaction, or via both a ring-opening polymerization reaction and a condensation reaction.

[0069]

[0069] The one or more non-biodegradable polyols may be polyether polyols. The polyether polyols may be one or more of glycerol ethoxylate, glycerol propoxylate, glycerol ethoxylate-co-propoxylate, glycerol ethoxylate-block-propoxylate, pentaerythritol ethoxylate, pentaerythritol propoxylate, and trimethylolpropane propoxylate.

[0070] The one or more non-biodegradable polyols may have a molecular weight of about 2000 daltons or less, or about 1500 daltons or less, or about 1300 daltons or less.

[0071]

[0071] The non-biodegradable polyol may have a molecular weight between about 200 and about 2,000 daltons, or between about 200 and about 1,500 daltons, or between about 200 and about 1,300 daltons, or between about 600 and about 1500 daltons, or between about 900 and about 1300 daltons.

[0072]

[0072] The non-biodegradable polyol may have a molecular weight of about 10,000 daltons or less, or about 8,000 daltons or less, or about 6,000 daltons or less, or about 4,000 daltons or less, or about 2,000 daltons or less, or about 1,500 daltons or less, or about 1,000 daltons or less, or about 800 daltons or less, or about 600 daltons or less, or about 500 daltons or less, or about 400 daltons or less, or about 350 daltons or less, or about 300 daltons or less.

[0073]

[0073] The non-biodegradable polyols may have a molecular weight of less than 500 daltons, or less than 400 daltons, or less than 350 daltons, or less than 300 daltons.

[0074]

[0074] Biodegradable polyols impart biodegradability to the foam. Polyols can be prepared by condensation polymerization or ring-opening polymerization with a high percentage of initiator (or starting agent) to control the molecular weight. The amount of initiator can range between 1 mole initiator per 200 g polyol to 1 mole initiator per 5000 g polyol, or between 1 mole initiator per 500 g polyol to 1 mole initiator per 2000 g polyol. Non-limiting examples of monomers suitable for initiators include pentaerythritol (4 arms), trimethylolpropane (3 arms), glycerol (3 arms), 1,4-butanediol (2 arms), myo-inositol (6 arms). Mixtures of initiators can be utilized. Mixtures of polyols can be utilized. It may be preferred to minimize the number of components. However, in some cases it may be advantageous to utilize more than one or more than two polyols. Polyols can have a hydroxyl functionality of 2 or more. Polyols with only a single hydroxyl functionality cannot produce suitable foams when used in large amounts. However, when used in small amounts, the properties of the foam can be adjusted, for example, adding a few percent of mono-hydroxyl compounds with long lipophilic chains can affect the hydrophobicity / hydrophilicity of the foam.

[0075] The decomposition rate of foam layer can be controlled by changing the ratio of biodegradable polyol to non-biodegradable polyol.By reducing or eliminating non-biodegradable polyol from the formulation, it can produce a foam layer that decomposes more quickly, which may be desirable in certain applications.The selection of monomer can also affect the decomposition rate due to the kinetic difference of the hydrolysis rate of different ester linkages.

[0076]

[0076] Biodegradable and non-biodegradable polyols have different functions in the foam layer of tissue repair laminate. Non-biodegradable polyols can be selected from polyether polyols, such as glycerol ethoxylate, glycerol propoxylate and glycerol ethoxylate-co-propoxylate. Such non-biodegradable polyols can stabilize foams through the introduction of non-biodegradable functional groups. In addition, they can provide a mechanism for controlling the hydrophilic / hydrophobic balance, for example, by the ethoxylate / propoxylate content. They can also improve the elasticity of foams by lowering the glass transition temperature (Tg).

[0077]

[0077] Biodegradable polyols can be solid at lower molecular weights than non-biodegradable polyols, for example, polycaprolactone diol of molecular weight 500 is solid at room temperature, while poly(propylene glycol) remains liquid until it reaches a much higher molecular weight. High molecular weight non-biodegradable liquid polyols can act as "fillers" to reduce the isocyanate content, thus reducing the possibility of scorching due to excessive exothermic reactions during foam preparation.

[0078]

[0078] Biodegradable polyols can be derived from one or more polyol initiators and at least one hydroxy acid and / or cyclic ester. They can contribute to the lowering of Tg in situations where the Tg was not lowered sufficiently by non-biodegradable polyethers. The polyol can be a three-armed polyol based on ε-caprolactone and one of glycolic acid or lactic acid, initiated with glycerol. The amount of CL: (LA and / or GA) can affect both the glass transition as well as the degradation time. More caprolactone lowers Tg and increases the degradation rate. The molecular weight can be 800-1200 Daltons. The molecular weight can be low enough to be liquid, but high enough that the reaction does not require a large amount of isocyanate to avoid scorch.

[0079] Isocyanate in the foam layer

[0079] The polyurethane for preparing the foam layer can be derived from one or more biodegradable polyols and one or more isocyanates. The molar ratio of isocyanate functional groups to hydroxy and other isocyanate-reactive functional groups for deriving the foam (isocyanate index) can be 1.0 or less, or 0.9 or less, or 0.8 or less, or 0.7 or less, or 0.6 or less. The isocyanate index can be between 0.4 and 1.0, or between 0.6 and 0.9.

[0080]

[0080] The polyurethane foams may be derived from polyols and isocyanates having an isocyanate content (i.e., content of NCO functional groups) of less than 20% by weight, or less than 19% by weight, or less than 18% by weight, or less than 17% by weight, or less than 16% by weight, or less than 15% by weight, or less than 14% by weight, or less than 13% by weight, or less than 12% by weight, or less than 11% by weight, or less than 10% by weight, or less than 9% by weight, or less than 8% by weight. The foams may have an isocyanate content of between 5% and 20% by weight, or between 8% and 17% by weight, or between 11% and 14% by weight, based on the total weight of the polyol and isocyanate.

[0081]

[0081] Decomposition products from aliphatic isocyanates (e.g., ethyl lysine diisocyanate (ELDI)) are generally considered to be more biocompatible than those from aromatic diisocyanates. Thus, isocyanates such as, for example, hexamethylene diisocyanate (HDI) and ELDI may be particularly suitable. Isophorone diisocyanate (IPDI) may also be used, but may impart a higher glass transition temperature, which may cause the foam to harden. Combinations of isocyanates may be used, and in some cases may be preferred, for example, a combination of HDI and IPDI to tailor the glass transition. Trimethylhexamethylene diisocyanate, 1,4-butane diisocyanate, methyl-lysine diisocyanate (MLDI) and other isocyanates commonly used in the synthesis of polyurethanes may also be suitable.

[0082]

[0082] A lower isocyanate index results in a softer, weaker foam layer that degrades more quickly. Increasing the isocyanate index may increase the decomposition time, but results in a stronger foam layer.

[0083]

[0083] Biodegradable polyurethane foams are advantageous because they can be designed to include properties such as elasticity, resistance to premature degradation, resistance to shrinkage, prevention of excessive acidic degradation products, biocompatibility, water absorption control, compatibility with other polyurethane layers, and ease of incorporating additives during synthesis. The foams are flexible and can be conformed to desired shapes.

[0084]

[0084] Foams can be designed to degrade at a particular rate. Foams can be designed to retain structural integrity for periods of time such as three months or longer, or can be designed to retain structural integrity for periods of time as short as a few days, or even a day or two.

[0085]

[0085] The polyurethane foam layer is capable of degrading under ASTM F1635 conditions such that the mass of the foam layer is reduced by between about 10% and about 90% in a period of one year or less.

[0086]

[0086] Alternatively, the mass of the foam layer can be reduced by between about 10% and about 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0087]

[0087] The rate of degradation under ASTM F1635 conditions can be controlled by varying the nature and ratio of polyurethane components. Thus, polyurethane can be designed to degrade within a specific period of time. This is advantageous to provide a material that can be partially, completely, or substantially completely degraded in a specific period of time, for example, when the functional aspect of the polyurethane foam layer is no longer required.

[0088]

[0088] This is particularly useful where the polyurethane is targeted for in vivo applications, since the polyurethane does not need to be surgically removed from the patient's body.

[0089]

[0089] The rate of degradation of the foam can be controlled by varying the ratio of biodegradable to non-biodegradable polyols or by selecting monomers. Reducing or eliminating non-biodegradable polyols from the formulation can produce a more rapidly degrading material, which may be desirable in certain applications.

[0090]

[0090] The foam may be derived from at least one prepolymer, which may be prepared by contacting one or more biodegradable polyols and / or one or more polyol initiators with one or more polyisocyanates. Non-limiting examples of polyol initiators are, for example, pentaerythritol, trimethylolpropane, glycerol, 1,4-butanediol and myo-inositol, ethylene glycol, sorbitol, glucose, sucrose, 1,2-propanediol, and mixtures thereof. The foam may be derived from a mixture of such prepolymers and further polyisocyanates thus formed. The foam may contain less than 50% by weight of prepolymer and more than 50% by weight of polyisocyanate, based on the combined weight of these components. The foam may contain less than 30% by weight of prepolymer and more than 70% by weight of polyisocyanate, based on the combined weight of these components. The foam thus prepared may advantageously have high strength and fine cell structure.

[0091]

[0091] The foam may be derived from a biodegradable polyol having a molecular weight of about 1300 Daltons or less, and from a polyol and a polyisocyanate having an isocyanate (NCO) content of less than 20% by weight, or less than 19% by weight, or less than 18% by weight, or less than 17% by weight, or less than 16% by weight, or less than 15% by weight, or less than 14% by weight, or less than 13% by weight, or less than 12% by weight, or less than 11% by weight, or less than 10% by weight, or less than 9% by weight, or less than 8% by weight, based on the total weight of the polyol and polyisocyanate.

[0092]

[0092] The foams may be derived from biodegradable polyols and non-biodegradable polyols, where the molecular weight of the biodegradable polyol is about 1300 Daltons or less, and from polyols and polyisocyanates having an isocyanate (NCO) content of less than 20% by weight, or less than 19% by weight, or less than 18% by weight, or less than 17% by weight, or less than 16% by weight, or less than 15% by weight, or less than 14% by weight, or less than 13% by weight, or less than 12% by weight, or less than 11% by weight, or less than 10% by weight, or less than 9% by weight, or less than 8% by weight, based on the total weight of the polyol and polyisocyanate.

[0093]

[0093] The foams may be derived from biodegradable polyols having a molecular weight of about 1300 Daltons or less, and having an isocyanate (NCO) content of less than 20% by weight, or less than 19% by weight, or less than 18% by weight, or less than 17% by weight, or less than 16% by weight, or less than 15% by weight, or less than 14% by weight, or less than 13% by weight, or less than 12% by weight, or less than 11% by weight, or less than 10% by weight, or less than 9% by weight, or less than 8% by weight, based on the total weight of the polyol and polyisocyanate, and having a molar ratio of isocyanate functional groups to hydroxy and other isocyanate-reactive functional groups (isocyanate index) of 1.0 or less.

[0094]

[0094] The foams may be derived from biodegradable and non-biodegradable polyols, where the molecular weight of the biodegradable polyol is about 1300 Daltons or less, and have an isocyanate (NCO) content of less than 20% by weight, or less than 19% by weight, or less than 18% by weight, or less than 17% by weight, or less than 16% by weight, or less than 15% by weight, or less than 14% by weight, or less than 13% by weight, or less than 12% by weight, or less than 11% by weight, or less than 10% by weight, or less than 9% by weight, or less than 8% by weight, based on the total weight of the polyol and polyisocyanate, and have a molar ratio of isocyanate functional groups to hydroxy and other isocyanate-reactive functional groups (isocyanate index) of 1.0 or less.

[0095]

[0095] Various additives known in the art of polyurethane foam technology and tissue engineering may be added to the foam. These additives may be added during or after the synthesis of the foam. In some cases, the additives may react during the synthesis of the foam and may be incorporated into the foam by covalent bonding. Exemplary additives include antimicrobial agents, plasticizers, pore openers, antioxidants, antistatic agents, catalysts, fillers, flame retardants, softeners / softeners, cell control agents, release agents, stabilizers, fillers, dyes, pigments, pigment dispersants, solvents, anesthetics, cells, enzymes, proteins, growth factors, growth inhibitors, hemostatic agents, and bioactive agents, such as drugs. The additives may or may not be chemically bound to the foam.

[0096] catalyst

[0096] A number of catalysts are known in the art of polyurethane synthesis that can be used to prepare the polyurethanes of the present disclosure. A variety of catalysts can be used to prepare the composition, and they can provide different attributes. Examples include dibutyltin dilaurate (DBTL), stannous octoate, and amine-based catalysts, such as DABCO. Bismuth, zinc, and titanium-based catalysts are also known to effectively catalyze urethane formation and exhibit low toxicity. COSCAT Z-22 is a zinc-based catalyst, and is an example of a catalyst that can be used that has low toxicity and produces effective results. Mercury and lead-containing catalysts, although effective, are considered toxic (non-biocompatible) and therefore not suitable. Combinations of catalysts are known to be effective. It is also desirable to minimize the amount of catalyst.

[0097] Surfactants

[0097] The function of the surfactant (stabilizer, blowing agent) is to help prevent the foam bubbles from bursting as they form during the reaction, thereby allowing the bubbles to form and create a stable foam which can then harden.

[0098]

[0098] The surfactant can be a siloxane-ether copolymer, a fluoro-ether copolymer, or other amphiphilic compound containing hydrophobic and hydrophilic moieties. Many surfactants are commercially available that are specifically developed for polyurethane foam. The amount used can vary from 0.01% to 1.5% of the total formulation weight. The preferred amount is in the range of 0.01% to 0.20% of the formulation. The most suitable amount depends on the molecular weight of the surfactant, as well as its composition and type, and the rest of the formulation. Some formulations may be more hydrophobic and some more hydrophilic, and therefore may require different amounts of stabilizer. Useful surfactants can be simple block copolymers and brush type copolymers. It is clear to one skilled in the art to vary the concentration of the surfactant and determine which concentration is most effective in stabilizing the foam layer.

[0099] Foaming Agent

[0099] The foam may be foamed by any method known in the art. The blowing agent may be generated during the formation of the foam and / or may be added as one or more additional components. Water may be used in the formulation to react with the isocyanate to form urea linkages and CO2 gas. The CO2 gas creates the bubbles and expands the foam. The temperature, mixture and selection of surfactants, for example, can all affect the size of the bubbles (cell size). Commercially, polyurethane foams range in pore size from microporous (low density shoe soles) to open cell large cell foams (e.g., in filters or foam mattresses). The desired porosity can be obtained by using 0.1-4 wt% water, preferably 1.0-1.5 wt% water in the overall formulation. This provides an appropriate level of foaming. Less water results in a denser foam. Higher amounts of water can be useful in some cases, but with the limitation that mechanical properties are negatively affected and scorching is more likely to occur.

[0100] [000100] Pentane and other low boiling point hydrocarbons may also be suitable as blowing agents. Foams produced in this manner may advantageously be free of urea due to the absence of water. Desirably, the absence of water reduces the amount of isocyanate required to react in the formulation, which in turn reduces the amount of heat generated when the foam is produced. This is particularly advantageous in large scale preparations where it may be more difficult for the reaction heat to dissipate from the foam.

[0101] [000101] The foam layer can include any one or more of the features disclosed herein in any combination.

[0102] Preparation of polyurethane for foam layer [000102] The foams can be prepared simply by a one-pot process. All components can be combined and mixed, with or without the application of heat, which results in the foam and cures. Alternatively, the foams may be prepared by any of the continuous or semi-continuous processes known in the art.

[0103] [000103] In one embodiment, one or more polyols or polyol initiators are first treated with a polyisocyanate to form a prepolymer. This prepolymer is then treated with additional components to form the foam. In another embodiment, additional polyisocyanates may be utilized in addition to those utilized to form the prepolymer.

[0104] [000104] In another embodiment, all components except the polyisocyanate component are mixed together to form one part. The polyisocyanate is then added to start the reaction. This has the advantage that the two parts are both stable before they are mixed together.

[0105] [000105] The foams may be prepared by a solvent-free process.

[0106] [000106] The foams can be advantageously prepared by a one-pot batch procedure that may not require isolation or purification of intermediate materials. The foams can be prepared from low cost raw materials.

[0107] Reticulation [000107] In some cases it may be advantageous to reticulate the foam. Reticulation removes cell membranes and increases the amount of open cell material. This can be advantageous when fluid movement is required. This can be done in a special chamber (reticulation chamber) where hydrogen and oxygen are introduced to the foam and burned to break down and remove any cell membranes.

[0108] [000108] Cell openers or cell opening agents may be added to the foam mixture, for example, to break down the pore structure during the foaming process, thereby creating a foam with a natural sponge structure. The cell opener can reduce the foam's firmness and shrinkage to produce a dimensionally stable foam with interconnected pores. Cell openers and other reactive components of polyurethane foams are discussed, for example, in Szycher, M, Szycher's Handbook of Polyurethanes, CRC Press, New York, NY, 9-6 to 9-8 (1999). Cell openers suitable for use include powdered divalent metal salts of long chain fatty acids having about 1 to 22 carbon atoms. Divalent metal salts of stearic acid, such as calcium stearate and magnesium stearate, are examples of cell openers. The concentration of the cell opener in the resin mixture can be in the range of approximately 0.1 to 7.0% by weight or in the range of approximately 0.3 to 1% by weight.

[0109] Bioactive Agents [000109] Bioactive agents may optionally be added to the foam mixture. As used herein, the term "bioactive agent" generally refers to an agent, molecule, or compound that affects the biological or chemical events of the host.

[0110] Barrier Layer [000110] The barrier layer of the tissue repair laminate of the present disclosure can be substantially resistant to adhesions to sensitive tissues and organs. The barrier layer can be non-adhesion forming or substantially non-adhesion forming.

[0111] [000111] The barrier layer may be composed of two or more layers. For example, the barrier layer may be a laminate of two or more sheets of the same or different polyurethanes.

[0112] [000112] In some embodiments, the polyurethane of the barrier layer comprises an expanded polyurethane.

[0113] [000113] In some embodiments, the oriented polyurethane comprises a biaxially oriented polyurethane.

[0114] [000114] In some embodiments, the expanded polyurethane is annealed.

[0115] [000115] The barrier layer should be flexible enough to conform to the shape of the foam layer. The barrier layer may be composed of one or more polyurethane layers.

[0116] [000116] The barrier layer can be biodegradable or non-biodegradable, but should preferably be biocompatible.

[0117] [000117] The barrier layer can be a thermoformed sheet.

[0118] [000118] The barrier layer may be formed by melt pressing.

[0119] [000119] The barrier layer may be formed by casting a film.

[0120] [000120] The barrier layer may be oriented in either one or two directions.

[0121] [000121] The barrier layer provides strength to the tissue repair laminate. In one preferred embodiment, the stretch barrier layer provides high strength to the tissue repair laminate.

[0122] [000122] The barrier layer can be a woven or nonwoven fabric of fibers that prevent tissue adhesions, for example obtained by electrospinning.

[0123] [000123] A barrier layer thickness of 50-400 μm provides a good balance of strength (which increases with thickness), permeability (which decreases with thickness), and handling (which becomes more difficult with increasing thickness). Furthermore, the mass of the barrier layer may be too large compared to the mass of the foam layer if the barrier layer is too thick.

[0124] [000124] The tissue repair laminate can include a biocompatible and / or biodegradable adhesive positioned between the foam layer and the barrier layer.

[0125] [000125] In other embodiments, no adhesive may be utilized and the barrier layer may be melted directly onto the foam layer.

[0126] Barrier layer polyurethane [000126] The barrier layer may include a biodegradable polyurethane. The barrier layer may be derived from one or more polyols, one or more isocyanates, and one or more chain extenders. The chain extenders may be biodegradable or non-degradable, and preferably the chain extenders include biodegradable chain extenders.

[0127] [000127] The polyurethane of the barrier layer may comprise one or more chain extenders represented by formula (1) or formula (2): one or more aliphatic polyester polyols, and One or more aliphatic diisocyanates It can be derived from

[0128] [ka]

[0023] wherein R1, R2 and R3 are optionally substituted C 1~20 Alkylene and optionally substituted C 2~20 alkenylene.]

[0129] [000128] The polyurethane of the barrier layer may have a number average molecular weight (M) of up to 200,000 daltons, or up to 150,000 daltons, or up to 100,000 daltons, or up to 60,000 daltons, or up to 40,000 daltons, or up to 20,000 daltons. w ).

[0130] [000129] The polyurethane of the barrier layer has a number average molecular weight (M) of between 2,000 and 200,000 daltons, or between 5,000 and 150,000 daltons, or between 10,000 and 100,000 daltons, or between 20,000 and 100,000 daltons, or between 2,000 and 60,000 daltons, or between 2,000 and 40,000 daltons, or between 2,000 and 20,000 daltons. w ).

[0131] [000130] The polyurethanes may have a number average molecular weight (M) of up to 100,000 daltons, or up to 75,000 daltons, or up to 50,000 daltons, or up to 30,000 daltons, or up to 20,000 daltons, or up to 10,000 daltons. n Preferably, the number average molecular weight of the polyurethane is between 50,000 and 100,000 Daltons.

[0132] [000131] The polyurethane may have a polydispersity (M) between 1.0 and 4.0, or between 1.0 and 3.5, or between 1.5 and 3.0. w / M n ) Preferably, the polydispersity is between 1.0 and 2.0.

[0133] Barrier Layer Polyol [000132] The polyol can include one or more polyester polyols.

[0134] [000133] The polyol may have a molecular weight between about 200 and about 2,000 daltons, or between about 200 and about 1,500 daltons, or between about 200 and about 1,300 daltons.

[0135] [000134] The polyol may have a molecular weight of about 10,000 daltons or less, or about 8,000 daltons or less, or about 6,000 daltons or less, or about 4,000 daltons or less, or about 2,000 daltons or less, or about 1,500 daltons or less, or about 1,000 daltons or less, or about 800 daltons or less, or about 600 daltons or less, or about 500 daltons or less, or about 400 daltons or less, or about 350 daltons or less, or about 300 daltons or less.

[0136] [000135] The polyol may have a molecular weight of less than 500 daltons, or less than 400 daltons, or less than 350 daltons, or less than 300 daltons.

[0137] [000136] The polyol can be in a liquid state at 20°C and atmospheric pressure. Alternatively, the polyol can be in a solid state at 20°C and atmospheric pressure.

[0138] [000137] The polyols can be derived from one or more diol initiators and one or more hydroxy acids, diacids or cyclic esters, and combinations thereof.

[0139] [000138] In one embodiment, the polyol can be derived from one or more diol initiators and at least one hydroxy acid.

[0140] [000139] In one embodiment, the polyol can be derived from one or more diol initiators and at least one diacid.

[0141] [000140] In one embodiment, the polyol can be derived from one or more diol initiators and at least one cyclic ester.

[0142] [000141] In one embodiment, the polyol can be derived from one or more diol initiators, at least one hydroxy acid, and at least one diacid.

[0143] [000142] In one embodiment, the polyol can be derived from one or more diol initiators, at least one hydroxy acid, and at least one cyclic ester.

[0144] [000143] In one embodiment, the polyol can be derived from one or more diol initiators, at least one diacid, and at least one cyclic ester.

[0145] [000144] In one embodiment, the polyol may be derived from one or more diol initiators, at least one hydroxyl acid, at least one diacid, and at least one cyclic ester.

[0146] [000145] Non-limiting examples of the one or more diol initiators include ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, pentanediol, hexamethylenediol, heptanediol, octanediol, nonanediol, decanediol, dodecanediol, 2-ethyl-1,3-hexanediol (EHD), 2,2,4-trimethylpentane-1,3-diol (TMPD), 1,4-cyclohexanedimethanol, diethylene glycol, dipropylene glycol, and combinations thereof. Non-limiting examples of diacids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, and hexadecanedioic acid, and combinations thereof. Exemplary hydroxy acids include l-lactic acid, d-lactic acid, d,l-lactic acid, mandelic acid, phenyl-lactic acid, hydroxybutyric acid, hydroxyvaleric acid, or glycolic acid, and combinations thereof. Non-limiting examples of cyclic esters include ε-caprolactone, glycolide, lactide, mandelide, and ρ-dioxanone, and combinations thereof. Polyols can be prepared via ring-opening polymerization or condensation reactions, or via both ring-opening polymerization and condensation reactions.

[0147] Chain extender for barrier layer [000146] In some embodiments, R1, R2, and R3 of formulas (1) and (2) are independently selected from optionally substituted C1-6 alkylene and optionally substituted C2-6 alkenylene.

[0148] [000147] The term "optionally substituted" includes C1-6 alkyl, C2-6 alkenyl, C2-6 alkynyl, halo, haloC1-6 alkyl, haloC2-6 alkenyl, haloC2-6 alkynyl, hydroxy, C1-6 alkoxy, C2-6 alkenyloxy, haloC1-6 alkoxy, haloalkenyloxy, nitro, nitroC1-6 alkyl, nitroC2-6 alkenyl, nitroC-6 alkynyl, nitroheterocyclyl, amino, C1-6 alkylamino, C1-6 dialkylamino, C2-6 alkynyl, C2-6 alkynyl, hydroxy, C1-6 alkoxy, C2-6 alkenyloxy, haloC1-6 alkoxy, haloalkenyloxy, nitro, C1-6 alkyl, nitroC2-6 alkenyl, nitroC-6 alkynyl, nitroheterocyclyl, amino, C1-6 alkylamino, C1-6 dialkylamino, C2-6 alkynyl, C2-6 alkynyl, hydroxy, C1-6 alkoxy, C2-6 alkenyloxy, haloC1 ... alkynyloxy, haloC1-6 alkynyl, "C1-6 alkylsulfonyl" refers to a group which may be unsubstituted or further substituted with one or more groups selected from arylamino, C2-6 alkynylamino, acyl, alkenylacyl, alkynylacyl, acylamino, diacylamino, acyloxy, C1-6 alkylsulfonyloxy, heterocyclyl, heterocyclyloxy, heterocyclylamino, haloheterocyclyl, C1-6 alkylsulfenyl, carboalkoxy, mercapto, C1-6 alkylthio, acylthio, phosphorus-containing groups, etc. Preferred optional substituents are methyl, ethyl, propyl, butyl, and phenyl.

[0149] [000148] The chain extenders of formula (1) or formula (2) are preferably hydroxy-acetic acid 3-hydroxy-propyl ester, 6-hydroxy-hexanoic acid 2-hydroxyethyl ester, 6-hydroxy-hexanoic acid 4-hydroxybutyl ester, ethylene glycol succinic acid diester diol, ethylene glycol fumaric acid diester diol, glycolic acid-ethylene glycol dimer and lactic acid-ethylene glycol dimer, and mixtures thereof.

[0150] [000149] Chain extenders of formula (1) or formula (2) can be prepared from one or more diols and one or more hydroxy acids, and / or cyclic esters.

[0151] [000150] Non-limiting examples of the one or more diols include ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, pentanediol, hexamethylenediol, heptanediol, octanediol, nonanediol, decanediol, dodecanediol, 2-ethyl-1,3-hexanediol (EHD), 2,2,4-trimethylpentane-1,3-diol (TMPD), 1,4-cyclohexanedimethanol, diethylene glycol, dipropylene glycol, and combinations thereof. Non-limiting examples of hydroxy acids include l-lactic acid, d-lactic acid, d,l-lactic acid, mandelic acid, phenyl-lactic acid, hydroxybutyric acid, hydroxyvaleric acid, or glycolic acid, and combinations thereof. Non-limiting examples of cyclic esters include ε-caprolactone, glycolide, lactide, mandelide, and ρ-dioxanone, and combinations thereof.

[0152] [000151] The polyurethane may further comprise one or more aliphatic polyol chain extenders that are not hydrolytically degradable under in vivo conditions. For example, the polyurethane may further comprise one or more diol chain extenders that do not contain ester functional groups in the backbone. Preferably, the non-degradable chain extenders are alkanediols having up to 30 carbon atoms, such as ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, pentanediol, hexamethylenediol, heptanediol, nonanediol, dodecanediol, 2-ethyl-1,3-hexanediol (EHD), 2,2,4-trimethylpentane-1,3-diol (TMPD), 1,6-hexanediol, 1,4-cyclohexanedimethanol, diethylene glycol, dipropylene glycol, and mixtures thereof.

[0153] Diisocyanate in Barrier Layer [000152] The aliphatic diisocyanate is preferably 4,4'-methylenedicyclohexyl diisocyanate (HMDI), 1,6-hexane diisocyanate (HDI), 1,4-butane diisocyanate (BDI), L-lysine diisocyanate (LDI), ethyl-L-lysine diisocyanate (ELDI), methyl-L-lysine diisocyanate (MLDI), 2,4,4-trimethylhexamethylene diisocyanate, other similar diisocyanates, and mixtures thereof.

[0154] [000153] Decomposition products from aliphatic isocyanates (e.g., ethyl lysine diisocyanate (ELDI)) are generally considered to be more biocompatible than those from aromatic diisocyanates. Thus, isocyanates such as hexamethylene diisocyanate (HDI) and ELDI may be particularly suitable. Isophorone diisocyanate (IPDI) may also be used. Combinations of isocyanates may be used and may be preferred in some cases, for example, combinations of HDI and IPDI to tailor the glass transition. Trimethylhexamethylene diisocyanate, 1,4-butane diisocyanate, methyl-lysine diisocyanate (MLDI) and other isocyanates commonly used in polyurethane synthesis may also be suitable.

[0155] Decomposition of polyurethane in the barrier layer [000154] Polyurethanes may contain hard and soft segments. The ratio of hard to soft segments affects the melting point of the polyurethane.

[0156] [000155] The hard segment content (HS%) of the polyurethane (i.e., the total content, expressed as a percentage by weight, of components derived from the chain extender of Formula (1) or Formula (2) and the isocyanate) can range from 2 to 100 wt%, or from 5 to 80 wt%, or from 10 to 70 wt%.

[0157] [000156] The soft segment content (SS%) of the polyurethane (i.e., the weight percentage of the component derived from the polyester polyol) can range from 5 to 98%, and in some embodiments is at least 25% or at least 40%.

[0158] [000157] In some embodiments, the polyurethane comprises hard segments and soft segments, and the hard segment content (HS%) of the polyurethane is less than 60%, preferably between 30-60%.

[0159] [000158] The amount of chain extender of formula (1) or formula (2) in the polyurethane can be varied to vary the non-degradable length of the continuous urethane in the hard segments. For example, the non-degradable length of the hard segments may have an average molecular weight between 100 and 10,000 daltons, or between 200 and 5,000 daltons, or between 400 and 2,000 daltons, or between 200 and 700 daltons, or between 320 and 700 daltons.

[0160] [000159] The polyurethane of the barrier layer is a polyurethane having a number average molecular weight (M n ) can be reduced by between 10% and 90% and / or the mass of the barrier layer can be decomposed such that it is reduced by between 10% and 90%.

[0161] [000160] The polyurethane of the barrier layer may be degradable in vivo. The polyurethane may be degradable at a temperature between 35 and 42°C.

[0162] [000161] Alternatively, the number average molecular weight (M) of the polyurethane decreases over a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less. n ) can be reduced by between 10% and 90% and / or the mass of the barrier layer can be reduced by between 10% and 90%.

[0163] [000162] The rate of degradation can be controlled by varying the nature and ratio of the polyurethane's components under ASTM F1635 conditions. Thus, polyurethanes can be designed to degrade within a specific period of time. This is advantageous in providing materials that can be partially, completely, or substantially completely degraded in a specific period of time, for example when the functional aspects of the polyurethane are no longer required.

[0164] Melting point [000163] The melting point of the polyurethane of the barrier layer may be between 60°C and 190°C. The melting point may be between 60°C and 180°C, or between 60°C and 170°C, or between 60°C and 160°C, or between 60°C and 150°C, or between 60°C and 140°C, or between 60°C and 130°C, or between 60°C and 120°C, or between 60°C and 110°C, or between 60°C and 100°C, or between 60°C and 100°C, or between 60°C and 90°C, or between 60°C and 80°C, or between 60°C and 70°C.

[0165] [000164] If a distinct melting transition occurs, the melting point can be determined by differential scanning calorimetry. Other techniques known to those skilled in the art can also be used, such as dynamic mechanical thermal analysis.

[0166] Preparation of the Laminate [000165] The barrier layer may be laminated to the foam layer by a combination of heat and pressure.

[0167] [000166] The barrier layer may be laminated to the foam layer such that there are substantially no voids (e.g., air bubbles) between the materials.

[0168] [000167] The foam layer and the barrier layer may have substantially equal length and width dimensions. The barrier layer may have a larger length and / or width dimension than the foam layer.

[0169] [000168] The barrier layer may be laminated to the foam layer by application of heat or pressure, or a combination of heat and pressure, through an interaction between the two materials. Alternatively, the barrier layer may be covalently bonded to the foam layer. In alternative and / or additional embodiments, the barrier layer may be laminated to the foam layer using a suitable adhesive according to any of the previous embodiments.

[0170] [000169] The second surface of the barrier layer may be made substantially flat or substantially non-tissue adhesive by pressing against a flat surface. For example, the second surface of the barrier layer may be pressed against a PTFE surface. Preferably, the pressing operation is performed when the polyurethane of the barrier layer is viscous.

[0171] [000170] Thus, in another aspect of the present disclosure, there is provided a method of preparing a tissue repair laminate, comprising: (a) melt pressing a polyurethane resin to form a barrier layer having oppositely facing first and second major surfaces; (b) applying a polyurethane foam layer having oppositely facing first and second major surfaces to a first major surface of the barrier layer; (c) fusing the foam layer and the barrier layer together by applying heat to the second major surface of the barrier layer; A method is provided, comprising:

[0172] [000171] Preferably, the barrier layer has a thickness between 0.03 and 1 mm.

[0173] [000172] Preferably, the foam layer has a thickness between 0.2 and 5 mm.

[0174] [000173] The melt pressing can be carried out at a temperature between 100 and 200°C.

[0175] [000174] Melt pressing can be carried out at pressures up to 30 tons.

[0176] [000175] The melt pressing can be performed between two flat sheets. The sheets can be substantially flat, although some degree of surface texturing is permitted. The melt pressing can be performed between two PTFE sheets, such as a glass fiber reinforced PTFE sheet.

[0177] [000176] Fusing may be performed without the application of pressure.

[0178] [000177] Fusing may be accomplished by applying heat to the second major surface of the barrier layer, for example by exposing the second major surface to a temperature between 100-200°C.

[0179] [000178] Fusion may be carried out for a period of time ranging from 5 seconds to several minutes, preferably from 15 seconds to 90 seconds.

[0180] [000179] Alternatively, the barrier layer may be applied to the foam layer by spraying or spreading.

[0181] [000180] In other embodiments, the barrier layer may be formed by other thermal processing methods known in the art, such as cast extrusion and blown film extrusion.

[0182] [000181] In other embodiments, the foam can be bonded or fused to the barrier layer by calendaring with heat or with solvents, or using ultrasonic means.

[0183] [000182] Thus, the barrier layer can be bonded to the foam layer by ultrasonic welding, which is a particularly useful method of bonding layers where an oriented barrier layer is utilized.

[0184] [000183] Thus, in another aspect of the present disclosure, there is provided a method of preparing a tissue repair laminate, comprising: (a) providing an expanded barrier layer having first and second oppositely facing major surfaces; (b) applying a polyurethane foam layer to a first major surface of the barrier layer; (c) bonding the foam layer and the barrier layer together using ultrasonic welding; A method is provided, comprising:

[0185] [000184] A variety of adhesives can be utilized to secure the barrier layer to the foam layer. The adhesive layer can be a fused or discontinuous layer. Suitable adhesives include, but are not limited to, solvent-based adhesives, latex adhesives, pressure-sensitive adhesives, hot melt adhesives, and reactive adhesives, such as biodegradable or non-biodegradable thermosetting polyurethane reactive mixtures. Suitable pressure-sensitive adhesives include, but are not limited to, pressure-sensitive adhesives made from acrylics, natural latex, styrene-butadiene rubber, and recycled rubber. Suitable hot melt adhesives include, but are not limited to, polyamides, polyolefins, and poly(ethylene-co-vinyl acetate).

[0186] [000185] In one embodiment, the barrier layer can itself be an adhesive. In other embodiments, no adhesive may be utilized and the barrier layer is melted directly onto the foam layer.

[0187] [000186] In another aspect of the present disclosure, there is provided a use of a tissue repair laminate as disclosed herein for performing tissue repair.

[0188] [000187] In another aspect of the present disclosure, a method of performing tissue repair using a tissue repair laminate as disclosed herein is provided.

[0189] [000188] In another aspect, there is provided a method of repairing tissue damage in a subject in need thereof, comprising surgically implanting a tissue repair laminate disclosed herein at the site of tissue damage in the subject.

[0190] [000189] The injury can include, for example, a hernia, a ventral hernia, a rotator cuff injury, a pelvic organ prolapse, or a female uro-gynecological injury. The site of the injury can be, for example, a soft tissue, a mesenchymal tissue, an intraperitoneal tissue, a rotator cuff tissue, a pelvic tissue, or a female uro-gynecological tissue. The intraperitoneal tissue can be, for example, an abdominal wall tissue. The rotator cuff tissue can be, for example, a rotator cuff tendon. The pelvic tissue can be, for example, a bladder tissue. The female uro-gynecological tissue can be, for example, a urethral tissue. Thus, for example, the method can include surgically implanting a tissue repair laminate into a site of interest, for example, an intraperitoneal tissue, such as an abdominal wall tissue, having a hernia (e.g., a ventral hernia). Also for example, the method can include surgically implanting a tissue repair laminate, for example, a rotator cuff repair laminate, into a site of interest, for example, a rotator cuff tissue, such as a rotator cuff tendon, having a rotator cuff injury. Also for example, the method can include surgically implanting a tissue repair laminate, e.g., a pelvic organ prolapse repair laminate, into a site of the subject, e.g., pelvic tissue, such as bladder tissue, having a pelvic organ prolapse.Also for example, the method can include surgically implanting a tissue repair laminate, e.g., a female urinary reconstruction laminate, into a site of the subject, e.g., female urinary tissue, such as urethral tissue, having a female urinary injury.

[0191] [000190] The tissue repair laminates may also be useful to strengthen tissue in surgical procedures such as abdominoplasty, breast reconstruction, midline closure, lateral closure, hernia repair, retrorectus hernia repair, Rives-Stoppa procedure, incisional hernia, cosmetic surgery, and the like.

[0192] [000191] Further features and advantages of the present disclosure will be understood by reference to the following figures and detailed description. [Brief description of the drawings]

[0193] [Figure 1] [000192] Figure 1 is a schematic diagram of a laminate according to one embodiment of the disclosure. [Diagram 2] [000193] Figure 2 is an exploded view of a laminate according to one embodiment of the disclosure. [Diagram 3] [000194] Figure 3 is an exploded view of a laminate according to one embodiment of the disclosure. [Figure 4] [000195] Figure 4 is a bar graph showing the results of graft size after 14 days in vivo. [Diagram 5] [000196] Figure 5 is a bar graph showing adhesion volume results. [Figure 6] [000197] Figure 6 is a bar graph showing adhesion type results. [Figure 7] [000198] Figure 7 shows a stress strain curve of a laminate according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0194] [000199] The following is a detailed description of the present disclosure provided to assist those skilled in the art in practicing the present disclosure. Those skilled in the art may modify and change the embodiments described herein without departing from the spirit or scope of the present disclosure.

[0195] [000200] Although any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of this disclosure, the preferred methods and materials are now described.

[0196] [000201] It should also be noted that as used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless specifically stated otherwise. Thus, for example, reference to a "chain extender" can include two or more chain extenders, and so forth.

[0197] [000202] Throughout this specification, the terms "comprises" or "comprising" or grammatical variations thereof are to be construed as specifying the presence of stated features, integers, steps or components, but not excluding the presence or addition of one or more other such features, integers, steps, components or groups not specifically mentioned.

[0198] [000203] Unless otherwise defined, all technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0199] [000204] As used herein, unless specifically stated or clear from the context, the term "about" is understood to be within a certain range of normal tolerances in the art, such as within two standard deviations (2 sigma) of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, or 0.01% of the stated value. Unless otherwise clear from the context, in this specification and claims, all numerical values ​​presented herein can be modified by the term "about".

[0200] [000205] Ranges provided herein are understood to be shorthand for all values ​​within the range. For example, a range of 1 to 50 is understood to include any number, combination of numbers, or subranges from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50.

[0201] [000206] The main components and features used in the preparation of one or more embodiments of the tissue repair laminate as disclosed herein are discussed in detail in the following sections.

[0202] Certain embodiments [000207] In one embodiment, the present disclosure provides a polyurethane of a barrier layer comprising: one or more chain extenders selected from hydroxy-acetic acid 3-hydroxy-propyl ester, 6-hydroxy-hexanoic acid 2-hydroxyethyl ester, 6-hydroxy-hexanoic acid 4-hydroxybutyl ester, ethylene glycol succinic acid diester diol, ethylene glycol fumaric acid diester diol, glycolic acid-ethylene glycol dimer and lactic acid-ethylene glycol dimer, one or more aliphatic polyester polyols, and One or more aliphatic diisocyanates Derived from, The polyurethane of the barrier layer has a melting point between 60°C and 190°C; Under ASTM F1635 conditions, the number average molecular weight (M n ) and / or the polyurethane of the foam layer and the barrier layer degrades such that the mass of the foam layer is independently reduced by between 10% and 90% over a period of one year or less; A tissue repair laminate is provided.

[0203] [000208] In one embodiment, the present disclosure provides a polyurethane of a barrier layer comprising: one or more chain extenders selected from hydroxy-acetic acid 3-hydroxy-propyl ester, 6-hydroxy-hexanoic acid 2-hydroxyethyl ester, 6-hydroxy-hexanoic acid 4-hydroxybutyl ester, ethylene glycol succinic acid diester diol, ethylene glycol fumaric acid diester diol, glycolic acid-ethylene glycol dimer and lactic acid-ethylene glycol dimer, one or more aliphatic polyester polyols, and One or more aliphatic diisocyanates selected from 4,4'-methylenedicyclohexyl diisocyanate (HMDI), 1,6-hexane diisocyanate (HDI), 1,4-butane diisocyanate (BDI), L-lysine diisocyanate (LDI), 2,4,4-trimethylhexamethylene diisocyanate Derived from, The polyurethane of the barrier layer has a melting point between 60°C and 190°C; Under ASTM F1635 conditions, the number average molecular weight (M n ) and / or the polyurethane of the foam layer and the barrier layer degrades such that the mass of the foam layer is independently reduced by between 10% and 90% over a period of one year or less; A tissue repair laminate is provided.

[0204] [000209] In one embodiment, the present disclosure provides a polyurethane of a barrier layer comprising: one or more chain extenders selected from hydroxy-acetic acid 3-hydroxy-propyl ester, 6-hydroxy-hexanoic acid 2-hydroxyethyl ester, 6-hydroxy-hexanoic acid 4-hydroxybutyl ester, ethylene glycol succinic acid diester diol, ethylene glycol fumaric acid diester diol, glycolic acid-ethylene glycol dimer and lactic acid-ethylene glycol dimer, one or more aliphatic polyester polyols derived from one or more diol initiators and at least one hydroxy acid and / or cyclic ester; and One or more aliphatic diisocyanates selected from 4,4'-methylenedicyclohexyl diisocyanate (HMDI), 1,6-hexane diisocyanate (HDI), 1,4-butane diisocyanate (BDI), L-lysine diisocyanate (LDI), 2,4,4-trimethylhexamethylene diisocyanate Derived from, The polyurethane of the barrier layer has a melting point between 60°C and 190°C; Under ASTM F1635 conditions, the number average molecular weight (M n ) and / or the polyurethane of the foam layer and the barrier layer degrades such that the mass of the foam layer is independently reduced by between 10% and 90% over a period of one year or less; A tissue repair laminate is provided.

[0205] [000210] In one embodiment, the present disclosure provides a polyurethane of a barrier layer comprising: one or more chain extenders selected from hydroxy-acetic acid 3-hydroxy-propyl ester, 6-hydroxy-hexanoic acid 2-hydroxyethyl ester, 6-hydroxy-hexanoic acid 4-hydroxybutyl ester, ethylene glycol succinic acid diester diol, ethylene glycol fumaric acid diester diol, glycolic acid-ethylene glycol dimer and lactic acid-ethylene glycol dimer, One or more aliphatic polyester polyols derived from one or more diol initiators and at least one hydroxy acid, diacid or cyclic ester, or combinations thereof, wherein the one or more diol initiators are selected from the group consisting of ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, pentanediol, hexamethylenediol, heptanediol, nonanediol, dodecanediol, 2-ethyl-1,3-hexanediol (EHD), 2,2,4-trimethylpentane-1,3-diol (TMPD), 1,6-hexanediol, 1,4-cyclohexene-1,3-diol (CMPD), 1,6-hexanediol, 1,8-cyclohexene-1,4-diol, 1,8-cyclohexene-1,4-diol, 1,6-cyclohexene-1,4-diol, 1,8-cyclohexene-1,4-diol, 1,6-cyclohexene-1,4-diol, 1,4-cyclohexene-1,6-diol, 1,4-cyclohexene-1,4 ... xane dimethanol, diethylene glycol, dipropylene glycol, and combinations thereof; the at least one hydroxy acid is selected from l-lactic acid, d-lactic acid, d,l-lactic acid, mandelic acid, phenyl-lactic acid, valeric acid, or glycolic acid; the one or more diacids are selected from oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, and hexadecanedioic acid; and the cyclic ester is selected from ε-caprolactone, glycolide, lactide, mandelide, and ρ-dioxanone; and One or more aliphatic diisocyanates selected from 4,4'-methylenedicyclohexyl diisocyanate (HMDI), 1,6-hexane diisocyanate (HDI), 1,4-butane diisocyanate (BDI), L-lysine diisocyanate (LDI), 2,4,4-trimethylhexamethylene diisocyanate Derived from, The polyurethane of the barrier layer has a melting point between 60°C and 190°C; Under ASTM F1635 conditions, the number average molecular weight (M n ) and / or the polyurethane of the foam layer and the barrier layer degrades such that the mass of the foam layer is independently reduced by between 10% and 90% over a period of one year or less; A tissue repair laminate is provided.

[0206] [000211] In one embodiment, the present disclosure provides: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; The foam layer has an average pore size of greater than 75 μm; the second major surface of the barrier layer adheres less to tissue than the first major surface of the foam layer; A tissue repair laminate is provided.

[0207] [000212] In one embodiment, the present disclosure provides: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; The foam layer has an average pore size of more than 100 μm; the second major surface of the barrier layer adheres less to tissue than the first major surface of the foam layer; A tissue repair laminate is provided.

[0208] [000213] In one embodiment, the present disclosure provides: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a biodegradable polyurethane barrier layer having first and second major surfaces facing in opposite directions. 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; The foam layer has an average pore size of greater than 75 μm; the second major surface of the barrier layer adheres less to tissue than the first major surface of the foam layer; A tissue repair laminate is provided.

[0209] [000214] In one embodiment, the present disclosure provides: (a) a biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a biodegradable polyurethane barrier layer having first and second major surfaces facing in opposite directions. 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration; The foam layer has an average pore size of more than 100 μm; the second major surface of the barrier layer adheres less to tissue than the first major surface of the foam layer; A tissue repair laminate is provided.

[0210] biologically active substances [000215] Bioactive materials may optionally be added to the polyurethane of the foam layer, the barrier layer, or both layers.

[0211] [000216] Bioactive agents may be formulated with the polyurethane to form a composition. Formulation can be facilitated, for example, by melt processing, additive manufacturing, or dissolution in a suitable solvent.

[0212] [000217] Bioactive agents may be synthetic molecules, biomolecules, or multi-molecular components, including, but not limited to, enzymes, organic catalysts, ribozymes, organometallics, proteins, glycoproteins, peptides, polyamino acids, antibodies, nucleic acids, steroidal molecules, antibiotics, silver, silver oxide, antiviral drugs, antifungal drugs, anticancer drugs, analgesics, anti-rejection drugs, immunosuppressants, cytokines, carbohydrates, lipophobic substances, lipids, extracellular matrix and / or its individual components, demineralized bone matrix, hydroxyapatite, tricalcium phosphate, pharmaceuticals, chemotherapeutic drugs, and therapeutic drugs. Cellular and non-cellular biological entities, such as viruses, viral vectors, and prions, can also be bioactive agents. Bioactive agents may be chemically bound to polyurethanes.

[0213] [000218] The biological effects in humans or animals are for medical, therapeutic, cosmetic and veterinary purposes and include pharmaceuticals, including drugs, functional cosmetics, functional foods and nutritional supplements. It will be understood that some bioactive compounds may fall into more than one of these classes.

[0214] [000219] A wide range of bioactive agents can be incorporated into the polyurethanes of the present disclosure and, consequently, delivered using the tissue repair laminates as disclosed herein.

[0215] [000220] Examples include cardiovascular therapeutic drugs, particularly antihypertensives (e.g., calcium channel blockers or calcium antagonists) and antiarrhythmics; medications for congestive heart failure; cardiac inotropes; vasodilators; ACE inhibitors; diuretics; carbonic anhydrase inhibitors; cardiac glycosides; phosphodiesterase inhibitors; alpha-blockers; beta-blockers; sodium channel blockers; potassium channel blockers; beta-adrenergic agonists; platelet inhibitors; angiotensin antagonists; anticoagulants; thrombolytic agents; drugs for the treatment of bleeding; drugs for the treatment of anemia; thrombin inhibitors; anthelmintics; antibacterial agents; insulin; human growth hormone. monoclonal antibodies and peptides;vaccines;anti-inflammatory agents, in particular non-steroidal anti-inflammatory drugs (NSAIDs), more particularly COX-2 inhibitors;steroidal anti-inflammatory agents;prophylactic anti-inflammatory agents;anti-glaucoma agents;mast cell stabilizers;mydriatics;agents affecting the respiratory system;medicines for allergic rhinitis;alpha-adrenergic agonists;corticosteroids;medicines for chronic obstructive pulmonary disease;xanthine-oxidase inhibitors;anti-arthritic agents;agents for the treatment of gout;autacoids and autacoid antagonists;anti-mycobacterial agents;anti-fungal agents;antiprotozoal agents;anthelmintics;especially respiratory, herpes, sarcoids Antiviral agents for pyomegalovirus, human immunodeficiency virus and hepatitis infections;treatments for leukemia and Kaposi's sarcoma;pain management agents, especially opioids, anesthetics and analgesics;neuroleptics;sympathomimetic medications;adrenergic agonists;drugs affecting the uptake or release of neurotransmitters;anticholinergic medications;anti-hemorrhoidal treatments;agents for preventing or treating the effects of radiation or chemotherapy;adipogenic drugs;fat reducing treatments;anti-obesity peptides;anti-obesity agents, e.g. lipase inhibitors;sympathomimetics;for gastric ulcers and inflammation drugs for the treatment of, for example, proton pump inhibitors; prostaglandins; VEGF inhibitors; anti-dyslipidemic agents, in particular statins; drugs affecting the central nervous system (CNS), for example, antipsychotics, antiepileptics and anticonvulsants (anticonvulsants), psychotropic drugs, stimulants, anxiolytics and hypnotics, antidepressants; antiparkinsonian medications; hormones and fragments thereof, for example, sex hormones; growth hormone antagonists; gonadotropin releasing hormone and analogues thereof; steroid hormones and their antagonists; selective estrogen modulators; growth factors;antidiabetic medicines such as insulin, insulin fragments, insulin analogues, glucagon-like peptides and hypoglycemic agents;H1, H2, H3 and H4 antihistamines;peptide, protein, polypeptide, nucleic acid and oligonucleotide medicines;natural proteins, polypeptides, oligonucleotides and nucleic acids and analogues, fragments and variants of such similar compounds;medicines used to treat migraine;asthma medicines;cholinergic antagonists;glucocorticoids;androgens;antiandrogens;inhibitors of adrenocorticoid biosynthesis;medicines to treat osteoporosis such as biphosphonates;antithyroid medicines;cytokine agonists;cytokine antagonists;anticancer drugs;anti-Alzheimer's drugs;HMGCoA reductase inhibitors;fibrates;cholesterol absorption inhibitors;HDL cholesterol raising agents;triglyceride reducing agents;anti-aging or anti-wrinkle agents;precursor molecules for hormone production; Proteins, such as collagen and elastin;antimicrobial agents;anti-acne agents;antioxidants;hair treatments and whitening agents;sunscreens, sunblocks and filters;variants of human apolipoproteins;precursor molecules for hormone production;proteins and peptides thereof;amino acids;plant extracts, such as grape seed extract;DHEA;isoflavones;nutritional agents, including vitamins, phytosterols and iridoid gylcosides, sesquiterpene lactones, terpenes, phenolic glycosides, triterpenes, hydroquinone derivatives, phenylalkanones;antioxidants, such as retinol and other retinoids, including retinoic acid and coenzyme Q10;omega-3 fatty acids;glucosamine;nucleic acids, oligonucleotides, antisense medicines;enzymes;cytokines;cytokine analogues;cytokine agonists;cytokine antagonists;immunoglobulins;antibodies;antibody medicines;gene therapy drugs;lipoproteins;erythropoietin;vaccines;These include, but are not limited to, small molecule and polymeric therapeutics for the treatment or prevention of human and animal diseases such as allergies / asthma, arthritis, cancer, diabetes, growth dysfunction, cardiovascular disease, inflammation, immunological disorders, alopecia, pain, eye diseases, epilepsy, gynecological disorders, CNS diseases, viral infections, bacterial infections, parasitic infections, GI diseases, obesity, and haemological diseases;

[0216] [000221] It is understood that pharma- ceutically, nutraceutically, or cosmetically acceptable derivatives of bioactive substances are included within the scope of this disclosure.

[0217] [000222] The term "pharmaceutical, nutraceutical or cosmetically acceptable derivative" includes (but is not limited to) pharmaceutical, nutraceutical or cosmetically acceptable salts, esters, salts of such esters, ethers, or any other derivatives, including prodrugs and metabolites, that are capable of directly or indirectly providing a biologically active substance as described elsewhere herein upon administration to a subject (e.g., a patient, human or animal) in need thereof.

[0218] [000223] As used herein, the term "pharmaceutical, nutraceutical or cosmetically acceptable salt" refers to those salts which, within the scope of sound medical judgment, are suitable for use in contact with the tissues of humans and lower animals without undue toxicity, irritation or allergic response, commensurate with a reasonable benefit / risk ratio.

[0219] [000224] Pharmaceutically, nutraceutical or cosmetically acceptable salts are well known in the art.For example, SM Berge et al., J. Pharmaceutical Sciences, 66:1-1 9, 1977, describes in detail pharmaceutical, nutraceutical or cosmetically acceptable salts.

[0220] [000225] Examples of pharma- ceutically, nutraceutical or cosmetically acceptable non-toxic acid addition salts are the salts of amino groups formed with inorganic acids such as hydrochloric, hydrobromic, phosphoric, sulfuric and perchloric acids, or with organic acids such as acetic, oxalic, maleic, tartaric, citric, succinic or malonic acids, or by other methods used in the art, such as ion exchange.

[0221] [000226] Other pharma- ceutically acceptable salts include adipate, alginate, ascorbate, aspartate, benzenesulfonate, benzoate, bisulfate, borate, butyrate, camphorate, camphorsulfonate, citrate, cyclopentanepropionate, digluconate, dodecyl sulfate, ethanesulfonate, formate, fumarate, glucoheptanoate, glycerophosphate, gluconate, hernisulfate, heptanoate, hexanoate, hydroiodide, 2hydroxy-ethoxybenzoate, 2-hydroxy-2-propanesulf ... Examples of salts that can be used include benzenesulfonate, lactobionate, lactate, laurate, lauryl sulfate, malate, maleate, malonate, methanesulfonate, 2-naphthalenesulfonate, nicotinate, nitrate, oleate, oxalate, palmitate, pamoate, pectinate, persulfate, 3-phenylpropionate, phosphate, picrate, pivalate, propionate, stearate, succinate, sulfate, tartrate, thiocyanate, p-toluenesulfonate, undecanoate, valerate, and the like.

[0222] [000227] Representative alkali or alkaline earth metal salts include sodium, lithium, potassium, calcium, magnesium, etc. Further pharma- ceutically acceptable salts include non-toxic ammonium, quaternary ammonium, and amine cations, formed where appropriate using counterions such as halides, hydroxides, carboxylates, sulfates, phosphates, nitrates, lower alkylsulfonates, and arylsulfonates.

[0223] [000228] The term "pharmaceutical, nutraceutical or cosmeceutical acceptable ester" refers to an ester that is hydrolyzed in vivo, including esters that decompose readily in the human body to leave the parent compound or a salt thereof. Suitable ester groups include, for example, those derived from pharmaceutical, nutraceutical or cosmeceutical acceptable aliphatic carboxylic acids, particularly alkanes, alkenes, cycloalkanes and alkanedioics, where each alkyl or alkenyl moiety advantageously has 6 or fewer carbon atoms. Examples of esters include formates, acetates, propionates, butyrates, acrylates and ethylsuccinates.

[0224] [000229] The term "pharmaceutical, nutraceutical or cosmetically acceptable prodrug," as used herein, includes prodrugs of a biologically active substance, and where possible zwitterionic forms of the biologically active substance, that are suitable for use in contact with the tissue of a subject without undue toxicity, irritation or allergic response, within the scope of sound medical judgment, and that are effective for their intended use, consistent with a reasonable benefit / loss ratio.

[0225] [000230] The term "prodrug" refers to a compound that is rapidly transformed in vivo to yield the parent compound, for example by hydrolysis in blood. A thorough discussion is provided in T. Higuchi and V. Stella, Pro-drugs as Novel Delivery Systems, Vol. 14 of the ACS Symposium Series, and in Edward B. Roche, ed., Bioreversible Carriers in Drug Design, American Pharmaceutical Association and Pergamon Press, 1987.

[0226] [000231] The present disclosure is further not limited to the administration of only one biologically active substance. Two or more biologically active substances or other therapeutic compounds can be incorporated into the foam layer and / or barrier layer.

[0227] Decomposition [000232] The polyurethane of either the foam layer or the barrier layer, or both layers, of the tissue repair laminate of the present disclosure can be designed to degrade at a controlled rate in vivo or under in vivo conditions. The polyurethane can be degradable at temperatures between 35-42°C.

[0228] [000233] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 20% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0229] [000234] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 30% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0230] [000235] In some embodiments, the number average molecular weight (M n) and the mass of the foam layer may independently decrease by between 40% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0231] [000236] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently be reduced by between 50% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0232] [000237] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 60% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0233] [000238] In some embodiments, the number average molecular weight (M n) and the mass of the foam layer may independently be reduced by between 70% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0234] [000239] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently be reduced by between 80% and 90% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0235] [000240] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 20% and 70% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0236] [000241] In some embodiments, the number average molecular weight (M n) and the mass of the foam layer may independently decrease by between 30% and 70% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0237] [000242] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 40% and 70% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0238] [000243] In some embodiments, the number average molecular weight (M n ) and the mass of the foam layer may independently decrease by between 50% and 70% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0239] [000244] In some embodiments, the number average molecular weight (M n) and the mass of the foam layer may independently decrease by between 60% and 70% in a period of 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less.

[0240] [000245] Figure 1 shows a tissue repair laminate (1) according to one embodiment of the present disclosure, comprising a foam layer (2) and a barrier layer (3).

[0241] [000246] Figure 2 shows an exploded view of the tissue repair laminate of Figure 1, including a foam layer (2) and a barrier layer (3). The foam layer includes a first major surface (4) and a second major surface (5), and the barrier layer includes a first major surface (6) and a second major surface (7).

[0242] [000247] Figure 3 shows an exploded view of a tissue repair laminate according to another embodiment of the present disclosure including a foam layer (2), a barrier layer (3) and an intermediate adhesive layer (8). The foam layer includes a first major surface (4) and a second major surface (5), and the barrier layer includes a first major surface (6) and a second major surface (7).

[0243] [000248] The following examples describe the preparation and use of tissue repair laminates according to the present disclosure and are intended to illustrate the present disclosure. The examples should not be construed as limiting the scope of the disclosure in any way. EXAMPLES

[0244] Preparation of the foam layer [000249] Biodegradable polyurethane thermoset foams were prepared according to the present disclosure. The foams were cut into sheets of various thicknesses using conventional foam slicing equipment.

[0245] Preparation of the barrier layer Example 1: Synthesis of polyols [000250] Polyol was prepared by the condensation of L-lactic acid (LLA), ε-caprolactone (CL) and 1,4-butanediol (BDO). All components were weighed and placed in a glass reactor equipped with an agitator, nitrogen gas outlet, condenser, and heat source. The temperature was set between 130°C and 210°C, and the agitation and nitrogen flow were initiated. As the reaction proceeded, water was removed from the vessel using a condenser. The reaction was allowed to continue until completion was confirmed by residual acid measurements, at which point the polyol was cooled and stored for use.

[0246] [000251] A 30:70 weight ratio of LLA:CL was used with BDO initiator to prepare a -400 molecular weight polyol as described above.

[0247] [000252] Specifically, 3887 g of 1,4-butanediol (BDO), 3953 g of 90% lactic acid, and 10520 g of ε-caprolactone were added to a reactor equipped with a stirrer, a condenser, and a nitrogen atmosphere. The mixture was heated at 200°C until the acid number reached 1.9 mg / g KOH, after which the heater was removed.

[0248] Example 2: Synthesis of chain extender [000253] Chain extenders were prepared by ring-opening polymerization of ε-caprolactone (CL) and 1,4-butanediol (BDO) in a molar ratio of 1:5. The temperature was set between 130°C and 210°C under stirring and nitrogen. The reaction was allowed to continue until gas chromatography (GC) analysis confirmed the reaction to be complete, at which point the chain extenders were cooled and stored for use.

[0249] [000254] In one example, 706.5 g of ε-caprolactone and 2792.5 g of BDO were added to a reactor equipped with a heater and stirrer. The mixture was heated at 200°C until no more ε-caprolactone was detected by GC. GC testing of the product showed 67.9% BDO, 26.7% dimer and 3.8% trimer.

[0250] Example 3: Synthesis of prepolymer [000255] 6000.5 g of the polyol prepared above was charged to a reactor equipped with a stirrer and under a nitrogen atmosphere, and 3467.5 g of 1,6-hexane diisocyanate (HDI) was added. The mixture was heated to 60° C. and reached 90° C. due to the heat of reaction. The mixture was then cooled to 60° C. and 128.27 g of the chain extender prepared above and 0.2 g of catalyst were added. The exotherm reached 82° C. The NCO content of the prepolymer was found to be 7.607%.

[0251] Example 4: Polymer synthesis [000256] 9458.5g of the above prepared prepolymer was weighed into a 20 liter container and 771.5g of dry BDO was added along with 0.7g of zinc-based catalyst. The mixture was stirred and then poured into a PTFE-coated tray and cured in an oven at 120°C for 2 hours. The polymer was then granulated using a Zerma GSL180 / 300 granulator.

[0252] Example 5: Polymer synthesis (hard segment 42%) [000257] Under nitrogen and stirring, 3 kg of the polyol from Example 1 was combined with HDI (1.734 kg). BDO-CL (Example 2, 63.5 g) and organozinc catalyst were added with heating to complete the prepolymer, which was assayed for isocyanate content. This was then chain extended using BDO (407.6 g) and additional zinc catalyst. The stirred mixture was then poured into a PTFE-machined tray and cured in an oven at 120° C. for 2 hours. The cured polymer was then granulated.

[0253] Example 6: Cast Film for Barrier Layer [000258] The dried granulated polymer of Example 5 was extruded on a small scale cast film line equipped with an extruder and chill rolls to provide a continuous film between 235-420 μm thick. The temperature during extrusion was between 160-185°C and lower in the feed zone.

[0254] Example 7: Stretching - Machine Direction Stretching (MDO) [000259] The cast film of Example 6 (300 μm thick) was passed through a continuous stretcher (MDO) and stretched using heat (40° C.-90° C.). Stretch ratios up to 1:5.5 were used, with measured residual stretch ratios between 1:2.3 and 1:4. Stretching was performed in two ways: using rolls of prepared film and in-line with the immediate output of the cast film line fed into the continuous stretcher as a continuous process. Films were collected on separate rolls for each condition.

[0255] Example 8: Melt-pressed barrier layer [000260] Polymer granules prepared as in Example 4 were melt pressed between glass fiber reinforced PTFE sheets at 175°C under 10t pressure in a Carver melt press to form a 0.2mm thick film.

[0256] Example 9: Preparation of Laminate [000261] A 1 mm foam sheet (biodegradable polyester-urethane-urea thermoset foam) was applied on top of the melt-pressed barrier layer of Example 8 and heated without pressure at 175°C for 45 seconds on a melt-press platen to bond the two layers together. Laminate specimens were cut (3cm x 7cm) and individually heat sealed to two layers of medical grade packaging (oriented polyamide and foil pouches). Sterilized by gamma irradiation in excess of 25kGy.

[0257] [000262] After standing overnight at 37°C, the properties of the laminates were measured under both dry and wet conditions on an Instron 5566 mechanical testing machine and the results are summarized in Table 1.

[0258] [Table 1]

[0259] Example 10: Spunbond [000263] A spunbond polyurethane was prepared using the same polyurethane as the barrier layer prepared above.

[0260] [000264] Six batches of polyurethane were prepared and granulated using the method outlined above, with 7 kg of each batch blended together for a total of 41 kg. The material was extruded and calendered on a 1 m spunbond line.

[0261] [000265] The area weight (weight of fiber per unit area) of spunbond fiber (dry) is 198 g / m 2 was measured.

[0262] [000266] Specimens were cut for mechanical testing on an Instron 5566 mechanical testing machine. Specimens were placed in distilled water at 37°C overnight before testing. Table 2 summarizes the test results.

[0263] [Table 2]

[0264] Example 11: Warp knit [000267] A warp knit polyurethane was prepared using the same polyurethane as the barrier layer and spunbond prepared above.

[0265] [000268] The polyurethane was extruded in a conventional extruder equipped with a take-off system that included a heated godet. Multiple monofilaments were produced and tested. The results are summarized in Table 3.

[0266] [Table 3]

[0267] [000269] Multiple filaments were warp knit using a double knit pattern to produce a mesh that was then stentered. The mesh had curling issues that were not corrected by stentering. Mesh samples were wetted in water for 2 hours and then mechanically tested. The results are summarized in Table 4.

[0268] [Table 4]

[0269] Example 12: Ultrasonic welding [000270] A laminate was prepared using the film of Example 7, annealed at 70°C prior to use, and 2 mm thick foam (biodegradable polyester-urethane-urea thermoset foam). A foam sheet was placed on top of the stretched and annealed film and welded together with an ultrasonic probe (40 kHz probe, Dukane IQ) set at 3 Joules and 50 amplitude per weld. The sheets were welded in a square array (center to center) with 4 mm spot welds spaced 14 mm apart. Tensile specimens were prepared and tested with an Instron model 5566 (10 cm long, 2.6 cm wide, two columns of welds per specimen, 50 mm gauge length, 500 mm / min). The welds were solid and the film was flat on the unbonded side. The average mechanical properties of the laminate were as follows: Ultimate tensile strength 56.6 N / cm, elongation 126%. FIG. 7 shows the stress strain curve of the laminate.

[0270] Comparative Example 1: Mechanical Test Results [000271] Mechanical testing was performed on foam layers without the barrier layer present. Tests were performed on foam layers of thickness 2 mm, 3 mm and 4 mm, both wet and dry, at high and low strain rates. Table 5 summarizes the results for ball burst strength and stitch retention.

[0271] [Table 5]

[0272] [000272] The foam layer without the barrier layer performed very poorly compared to the ball burst strength and seam retention strength of the laminates in Table 1. Even a 4 mm thick foam layer performed very poorly compared to a laminate of a 1 mm foam layer with a 200 μm barrier layer.

[0273] In-Vivo Studies [000273] Twenty-five 3-month-old male New Zealand White rabbits were randomly assigned to five groups of five rabbits each. Five separate test articles were implanted to repair abdominal wall defects, including Prolene® (Ethicon), a monofilament non-biodegradable polypropylene mesh, three structural polyurethane articles (Test Samples A, B, and C), and AlloDerm® (Life Cell Corporation), a skin-derived extracellular matrix. The groups were: Group 1, Test A; Group 2, Test B; Group 3, Test C; Group 4, AlloDerm®, and Group 5, Prolene®.

[0274] [000274] Test A was a laminate according to the present disclosure. Comparative Test B was a spunbond polyurethane mesh, and Comparative Test C was a knitted polyurethane mesh. Each of the test pieces was 7 cm by 3 cm in size (surface area of ​​21 cm). 2 ).

[0275] [000275] On day 1 of the study, a veterinarian created a full thickness 7 x 3 cm abdominal wall defect in each rabbit and repaired the defect with the synthetic and biological materials described above. Test A (laminate of the present disclosure) was used with the foam layer facing the abdominal wall and the barrier layer facing the internal organs.

[0276] [000276] Two weeks after surgery (day 14), animals were sacrificed and assessed for the extent and severity of adhesion formation. The size and integrity of the grafts in the five experimental groups were analyzed and compared. Animals were carefully evaluated for the presence and degree of intraperitoneal adhesions, and graft size was measured to check for contraction, if any. Biopsies were obtained within 1 cm of the suture line and graft center and fixed for histopathology, including quantification of vascular elements, cellularity, collagen content, and inflammation. All sections were stained with hematoxylin and eosin (H&E). The scales in Tables 6 and 7 were used for adhesions.

[0277] [Table 6]

[0278] [Table 7]

[0279] [000277] Below is a summary of the tissue reactions observed with the devices used.

[0280] [000278] Group 1 (Study A): Adhesion scores (percent adhesion area) for animals 1001, 1002, 1003, 1004, and 1005 were 0, 0, 0.5, 0.5, and 0.5, respectively (mean=0.3), adhesion type scores were 0, 0, 0.5, 1, and 0.5, respectively (mean=0.4), and there were no abscesses. The only reason for adhesion scores above 0 was minor adhesions to the suture lines and not to the article itself.

[0281] [000279] Group 2 (Study B): The adhesion scores (percent adhesion area) for animals 2001, 2002, 2003, 2004, and 2005 were 4, 4, 2, 4, and 1, respectively (mean = 3.0), and the adhesion type scores were 3, 3, 3, 3, and 3, respectively (mean = 3.0), with no abscesses.

[0282] [000280] Group 3 (Study C): Adhesion scores (percent adhesion area) for animals 3001, 3002, 3003, 3004, and 3005 were 2, 4, 3, 4, and 4, respectively (mean 3.4), adhesion type scores were 2, 3, 3, 3, and 3, respectively (mean = 2.8), and there were no abscesses.

[0283] [000281] Group 4 (AlloDerm®): Adhesion scores (percent adhesion area) for animals 4001, 4002, 4003, 4004, and 4005 were 1, 1, 0, 0, and 0, respectively (mean=0.4), adhesion type scores were 1, 2, 0, 0, and 0, respectively (mean=0.6), and there were no abscesses. The only reason for adhesion scores above 0 was minor adhesions to the suture lines and not to the article itself.

[0284] [000282] Group 5 (Prolene®): Adhesion scores (percent area adhesions) for animals 5001, 5002, 5003, 5004, and 5005 were 4, 4, 4, 4, and 4, respectively (mean 4.0), adhesion type scores were 3, 3, 3, 3, and 3, respectively (mean = 3.0), and there were no abscesses. Most or all of the article surface was adhered to the large intestine.

[0285] [000283] Tables 8 and 9 summarize the average adhesion results and Figures 4 and 5 show the results graphically.

[0286] [Table 8]

[0287] [Table 9]

[0288] [000284] Based on the overall necropsy data, it is clear that Groups 1 and 4 (Test A and AlloDerm®, respectively) had significantly less and substantially less adhesions when compared to the other groups. Only two out of five animals in each of these groups had evidence of adhesions with small areas of adhesion to the sutures, but not to the article itself. Based on the overall adhesion scores, Group 1 (Test A) showed the least substantial adhesions compared to any other group. Groups 3 (Test C) and 5 (Prolene®) showed the most severe adhesion scores compared to the other groups. These results were supported by statistical analysis which revealed significant differences in adhesion amount and type scores between the groups when examined after splitting the groups into two sets containing Groups 2, 3, and 5, and Groups 1 and 4, respectively. No statistically significant differences were detected in adhesion amount or type scores between Groups 2, 3, and 5, although all three of these groups had significantly higher mean scores than Groups 1 and 4. Similarly, no statistically significant differences were detected in adhesion amount or type scores between groups 1 and 4, although both of these groups had significantly lower scores than groups 2, 3, and 5.

[0289] [000285] As shown in Table 10 and Figure 6, Group 1 (Study A) showed the least contraction compared to all other groups. Group 4 (AlloDerm®) showed the next least overall amount of contraction.

[0290] [Table 10]

[0291] [000286] Thus, the synthetic tissue repair laminates of the present disclosure performed exceptionally well and were effective with no tissue adhesion to the barrier layer surface and no shrinkage of the laminate. In particular, the laminate, spunbond and warp knit barrier layers were all formed from the same polyurethane resin, yet both the spunbond and warp knit were highly adhesive to tissue and showed significant shrinkage in vivo.

[0292] [000287] The contents of all references and published patents and patent applications cited throughout this application are incorporated herein by reference. Those skilled in the art will recognize that the disclosed structures, materials, compositions, and methods may be modified to practice the disclosure, and such modifications are deemed to be within the scope of the disclosure.

[0293] [000288] Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments and methods described herein which equivalents are intended to be encompassed by the following claims.

[0294] [000289] It is understood that the detailed examples and embodiments described herein are presented for illustrative purposes only and are not to be considered as limiting the present disclosure in any way. Various modifications or changes will be suggested to those skilled in the art in light of the present disclosure, and such modifications or changes are considered to be within the spirit and scope of the present application and within the scope of the appended claims. For example, the relative amounts of the components can be changed to optimize the desired effect, additional components can be added, and / or similar components can be substituted for one or more of the components described. Additional advantageous features and functionality associated with the systems, methods, and processes of the present disclosure will be apparent from the appended claims. Moreover, those skilled in the art will recognize or be able to ascertain, using no more than routine experimentation, many equivalents to the specific embodiments of the present disclosure described herein. Such equivalents are intended to be encompassed by the following claims.

Claims

1. (a) a thermosetting, biodegradable polyurethane foam layer having first and second oppositely facing major surfaces; and (b) a thermoplastic and biodegradable polyurethane barrier layer having first and second major surfaces facing in opposite directions; 1. A tissue repair laminate comprising: a first major surface of the barrier layer and a second major surface of the foam layer opposed to one another; the foam layer comprises a pore structure configured for cell infiltration and has an average pore size of greater than 75 μm, the foam of the foam layer being a non-reticulated foam; a second major surface of the barrier layer that is less adhesion forming than a first major surface of the foam layer; after 10 days under in vivo conditions, the tissue repair laminate shrinks less than 10% in surface area on any surface; The polyurethane barrier layer comprises: One or more chain extenders represented by formula (1) or formula (2): 【Chemistry 1】 [In the formula, R 1 , R 2 and R 3 is unsubstituted or substituted C 1~20 Alkylene and unsubstituted or substituted C 2~20 alkenylene; R 1 , R 2 and / or R 3 are substituted, each independently represents C1-6 alkyl, C2-6 alkenyl, C2-6 alkynyl, halo, halo C1-6 alkyl, halo C2-6 alkenyl, halo C2-6 alkynyl, hydroxy, C1-6 alkoxy, C2-6 alkenyloxy, halo C1-6 alkoxy, haloalkenyloxy, nitro, nitro C1-6 alkyl, nitro C2-6 alkenyl, nitro C-6 alkynyl, nitroheterocyclyl, amino, C1-6 alkylamino, C1-6 dialkyi, and is substituted with one or more groups selected from: arylamino, C2-6 alkenylamino, C2-6 alkynylamino, acyl, alkenylacyl, alkynylacyl, acylamino, diacylamino, acyloxy, C1-6 alkylsulfonyloxy, heterocyclyl, heterocyclyloxy, heterocyclylamino, haloheterocyclyl, C1-6 alkylsulfenyl, carboalkoxy, mercapto, C1-6 alkylthio, acylthio, and a phosphorus-containing group. one or more aliphatic polyester polyols, and One or more aliphatic diisocyanates Derived from Tissue repair laminate.

2. 10. The tissue repair laminate of claim 1, wherein the polyurethane foam layer has an average pore size greater than 100 μm, or greater than 200 μm, or greater than 300 μm, or greater than 400 μm.

3. The tissue repair laminate of claim 1 or 2, wherein the average pore size of the polyurethane foam layer is between 100 and 300 μm.

4. 3. The tissue repair laminate of claim 1 or 2, wherein the tissue repair laminate shrinks by less than 5% in any surface area after 10 days under in vivo conditions.

5. the foam layer has a thickness between 0.1 mm and 10 mm, or between 0.2 mm and 5 mm, or between 0.3 mm and 3 mm, or between 0.3 mm and 2 mm; and / or the barrier layer has a thickness between 20 μm and 1000 μm, or between 50 μm and 500 μm, or between 50 μm and 400 μm; The tissue repair laminate according to any one of claims 1 to 4.

6. and / or, under ASTM F1635 conditions, the polyurethane foam layer degrades such that the mass of the foam layer is reduced by between 10% and 90% in a period of 1 year or less, or 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less. The number average molecular weight (M n the polyurethane barrier layer degrades such that the thermal conductivity of the polyurethane barrier layer is reduced by between 10% and 90% in a period of 1 year or less, or 11 months or less, or 10 months or less, or 9 months or less, or 8 months or less, or 7 months or less, or 6 months or less, or 5 months or less, or 4 months or less, or 3 months or less, or 2 months or less, or 1 month or less; The tissue repair laminate of any one of claims 1 to 5.

7. the polyurethane foam is derived from one or more biodegradable polyols and one or more isocyanates; or the polyurethane foam is derived from one or more biodegradable polyols, one or more isocyanates, and one or more non-biodegradable polyols; The tissue repair laminate according to any one of claims 1 to 6.

8. The tissue repair laminate of any one of claims 1 to 7, wherein the polyurethane of the barrier layer comprises an oriented polyurethane.

9. The polyurethane barrier layer has a number average molecular weight (M) of up to 200,000 Daltons, or up to 150,000 Daltons, or up to 100,000 Daltons, or up to 60,000 Daltons, or up to 40,000 Daltons, or up to 20,000 Daltons. n 9. The tissue repair laminate of claim 1, comprising:

10. The tissue repair laminate of any one of claims 1 to 9, wherein the polyester polyol is derived from one or more diol initiators and one or more hydroxy acids, diacids or cyclic esters, and combinations thereof.

11. The polyurethane barrier layer comprises a hard segment and a soft segment: the hard segment content (HS%) of said polyurethane is between 2 and 100 wt %, or between 5 and 80 wt %, or between 10 and 70 wt %; and / or the soft segment content (SS%) of said polyurethane is at least 25%, or at least 40%; and / or the hard segment content (HS%) of said polyurethane is less than 60% or between 30 and 60%; and / or the length of the non-degraded part of the hard segment has a molecular weight between 100 and 10,000 daltons, or between 200 and 5,000 daltons, or between 400 and 2,000 daltons, or between 200 and 1,000 daltons, or between 200 and 700 daltons, or between 320 and 700 daltons; The tissue repair laminate according to any one of claims 1 to 10.

12. A method for preparing the tissue repair laminate of any one of claims 1 to 11, comprising: (a) providing an oriented barrier layer having first and second oppositely facing major surfaces; (b) applying a polyurethane foam layer having oppositely facing first and second major surfaces to a first major surface of the barrier layer; (c) bonding the foam layer and the barrier layer together using ultrasonic welding; A method comprising:

Citation Information

Patent Citations

  • Biodegradable polyurethane / urea composition

    JP2006510747A

  • chain extender

    JP2009508598A